DETERMINANTS OF INVESTMENT DECISIONS OF YOUNG ENTREPRENEURS IN KUDUS DISTRICT THROUGH ONLINE SHARIA MUTUAL FUNDS - ELFAZ, MAULANISA ARIFA; PRAJASARI, ANNIZA CITRA (Business Management Analysis Journal (BMAJ), 2025)
The research aims to examine the influence of perceived ease of use, perceived benefits, and perceived risk on the investment decisions of young entrepreneurs in Kudus Regency through online sharia Sharia mutual funds, with digital literacy and sharia Sharia financial literacy as moderating variables. The sample consisted of 143 young entrepreneurs who had invested in online Sharia mutual funds. This research uses quantitative methods to test pathways. The research results show that perceived ease of use, perceived benefits, and perceived risk positively and significantly influence young entrepreneurs' investment decisions in Kudus Regency. However, digital literacy does not moderate the influence of perceived ease of use on investment decisions. On the other hand, Islamic financial literacy weakens the relationship between risk perception and investment decisions. Limitations of this study include the focus on a specific demographic and geographic region, which suggests that future research could explore different populations or regions to increase generalizability.